Study protocol: to investigate effects of highly specialized rehabilitation for patients with multiple sclerosis. A randomized controlled trial of a personalized, multidisciplinary intervention - Sørensen Jan; Lee Anne; Løvendahl Brita; Nørgaard Michael; Bay Jette; Rasmussen Peter; Boesen Finn (BMC, 2012)
Abstract Background Multiple sclerosis (MS) is a complex, chronic and progressive disease and rehabilitation services can provide important support to patients. Few MS rehabilitation programs have been shown to provide health improvements to patients in a cost-effective manner. The objective of this study is to assess the effects in terms of changes measured by a variety of standardized quality of life, mastery, coping, compliance and individual goal-related endpoints. This combination provides the basis for analyzing the complexity of MS and outcomes of a personalized rehabilitation. Methods/Design Patients with MS referred to hospital rehabilitation services will be randomized to either early admission (within two months) or usual admission (after an average waiting time of eight months). They will complete a battery of standardized health outcome instruments prior to randomization, and again six and twelve months after randomization, and a battery of goal-related outcome measures at admission and discharge, and again one, six and twelve months after randomization. Discussion The results of the study are expected to contribute to further development of MS rehabilitation services and to discussions about the design and content of such services. The results will also provide additional information to health authorities responsible for providing and financing rehabilitation services. Trial registration Current Controlled Trials (ISRCTN05245917)